2015
DOI: 10.1016/j.watres.2014.08.053
|View full text |Cite
|
Sign up to set email alerts
|

A review on emerging contaminants in wastewaters and the environment: Current knowledge, understudied areas and recommendations for future monitoring

Abstract: This review identifies understudied areas of emerging contaminant (EC) research in wastewaters and the environment, and recommends direction for future monitoring. Non-regulated trace organic ECs including pharmaceuticals, illicit drugs and personal care products are focused on due to ongoing policy initiatives and the expectant broadening of environmental legislation. These ECs are ubiquitous in the aquatic environment, mainly derived from the discharge of municipal wastewater effluents. Their presence is of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
893
2
68

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 2,160 publications
(1,064 citation statements)
references
References 157 publications
30
893
2
68
Order By: Relevance
“…Unfortunately, there are no legal limits for organic and emerging (compounds previously unknown or undetected; the term includes a large variety of products such as pharmaceuticals, veterinary products, pesticides, nanomaterials, etc.) contaminants (Petrie et al, 2015). In this respect, highest abundance values for the intl1 gene, related to class 1 integrons, were found in compost in pellet form and bokashi.…”
Section: Presence Of Contaminantsmentioning
confidence: 89%
“…Unfortunately, there are no legal limits for organic and emerging (compounds previously unknown or undetected; the term includes a large variety of products such as pharmaceuticals, veterinary products, pesticides, nanomaterials, etc.) contaminants (Petrie et al, 2015). In this respect, highest abundance values for the intl1 gene, related to class 1 integrons, were found in compost in pellet form and bokashi.…”
Section: Presence Of Contaminantsmentioning
confidence: 89%
“…BPA can also partially accumulate by passing through soil and river sediments. [15] 60-600 [43] 360-1620 [18] 378-890 [9] 416-2050 [23] 1800 [40] 2-44 [43] 30-1100 [15] 35-86 [23] 110-300 [18] 700 [40] 1.2-1900 [1] 2.1-87 [13] 2.2-4230 [21] 6-34 [23] 6-68 [11] 6-500 [26] 6-881 [22] 7.5-334 [12] 55-162 [27] 192-215 [15] 460-4800 [25] b.l.q.-494 [17] b.l.q.-7000 [19] b.l.q.-9300 [28] 1-1136 [20] 1-11 [4] 79-2550 [15] 600-11000 [14] 0.17-1.25 [2] 0.58-36700 [8] 1.1-43 [42] 4.3-130 [25] 10-530 [23] 53-196 [43] 0.32 [6] Fu and Kawamura [5] showed that bisphenol A is also present in air samples. In the agricultural areas of China, its concentration in the air does not exceed 240 pg/m3, but the air samples in urban areas are more contaminated (20-2.340 pg/m 3 ).…”
Section: Occurrence In the Environmentmentioning
confidence: 99%
“…CECs have received increasing attention during the last decades, and ways to remove them from the wastewater have been intensively researched (Petrie et al 2015 ).…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%
“…Petrie et al ( 2015 ) claimed that further studies, which combined the use of chemical and biochemical analysis to better assess the environmental risk, are required. Accordingly, the main purpose of this work was to determine appropriate photo-Fenton process variables for an efficient BPA mineralization performance, biodegradability increase, and toxicity removal.…”
Section: Electronic Supplementary Materialsmentioning
confidence: 99%